EFFORTS TO IMPROVE MATHEMATICAL LEARNING ACTIVITIES USING THE COOPERATIVE LEARNING MODEL OF TEAM ASSISTED INDIVIDUALIZATION (TAI) CLASS XI RPL SMK MUHAMMADIYAH KRETEK - Aang Kurniawan; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
This class action research aims to improve the learning activities of students of class XI RPL at SMK Muhammadiyah Kretek through Team Assisted Individualization (TAI) cooperative learning models. The research subjects were students in class XI RPL. Research instruments in the form of test questions, observation sheets, and interviews. Data analysis techniques using qualitative descriptive analysis. The results showed that the application of the TAI type of cooperative learning model could increase student mathematics learning activities. Cycle I obtained the percentage of enthusiastic aspects of students in taking lessons 50.781% with sufficient criteria. Aspects of student interaction with teachers 49.98% with sufficient criteria. Aspects of interaction between students 50.78% in the criteria sufficient. The aspect of group collaboration 52.343% in the criteria is sufficient. Aspects of student activity in groups of 49.98% insufficient criteria. The aspect of student participation in concluding the results of discussion 56.25% in the criteria is sufficient. So the learning activities of students in class XI RPL are 51.71% with sufficient criteria. Cycle II obtained the percentage of enthusiastic aspects of students in taking lessons 66,406% with good criteria. 64.063% aspects of student interaction with teachers with good criteria. Aspects of interaction between students 61,709% in good criteria. The aspect of group cooperation is 64,063% in good criteria. Aspects of student activity in groups 62.5% in good criteria. The aspect of student participation in concluding the results of the discussion was 65,625% in good criteria. So the learning activities of students in class XI RPL are 64,063% with good criteria.